A Socio-Legal Analysis of Inheritance Disputes in Indonesia - Ahmad Rifa'i; Abdulloh Abdulloh (al-Afkar, Journal For Islamic Studies, 2026)
This study examines the phenomenon of inheritance disputes, which are often viewed in a reductive manner as mere material conflicts, yet empirically serve as instruments for identity validation and the restoration of honor for men, thereby mitigating the risk of domestic violence that threatens public health stability. The purpose of this study is to reconstruct the meaning of kinship systems in Indonesia by uncovering the latent dimensions of inheritance disputes. Using a juridical-empirical method through a socio-legal approach, the analysis aims to identify mental health variables such as chronic stress and identity crises as they emerge in the literature of legal sociology. The research findings indicate that both Islam and customary law provide safety valve mechanisms such as the Qawwam principle, the tradition of migration, and reciprocal gifts that effectively reduce legal resistance by transforming men’s positions into authoritative, sovereign subjects. In conclusion, inheritance justice must be repositioned from a mere division of assets into a process of identity restoration that is crucial for the biopsychosocial stability of the family.